Non-verbal emotion communication training induces specific changes in brain function and structure - Kreifelts, Benjamin; Jacob, Heike; Brück, Carolin; Erb, Michael; Ethofer, Thomas; Wildgruber, Dirk (Frontiers in Human Neuroscience, 2013)
The perception of emotional cues from voice and face is essential for social interaction. However, this process is altered in various psychiatric conditions along with impaired social functioning. Emotion communication trainings have been demonstrated to improve social interaction in healthy individuals and to reduce emotional communication deficits in psychiatric patients. Here, we investigated the impact of a nonverbal emotion communication training (NECT) on cerebral activation and brain structure in a controlled and combined functional magnetic resonance imaging and voxel-based morphometry study. NECT-specific reductions in brain activity occurred in a distributed set of brain regions including face- and voice processing regions as well as emotion processing- and motor-related regions presumably reflecting training-induced familiarization with the evaluation of face/voice stimuli. Training-induced changes in nonverbal emotion sensitivity at the behavioral level and the respective cerebral activation patterns were correlated in the face-selective cortical areas in the posterior superior temporal sulcus and fusiform gyrus for valence ratings and in the temporal pole, lateral prefrontal cortex and midbrain/thalamus for the response times. A NECT-induced increase in grey matter volume was observed in the fusiform face area. Thus, NECT induces both functional and structural plasticity in the face processing system as well as functional plasticity in the emotion perception and evaluation system. We propose that functional alterations are presumably related to changes in sensory tuning in the decoding of emotional expressions. Taken together, these findings highlight that the present experimental design may serve as a valuable tool to investigate the altered behavioral and neuronal processing of emotional cues in psychiatric disorders as well as the impact of therapeutic interventions on brain function and structure.